Measuring Consumer Responses to Food Labels: A Descriptive Study - Clare , Greg (Emerging Challenges in Agriculture and Food Science Vol. 5, 2022)
Consumer responses to beef steak label information placement variations were measured in this study, which controlled for chromaticity. To measure information flow to consumers across label variations, eye tracking and scan path entropy have been used. In the placement variations, safe handling messages had the lowest entropy. Except when the monochrome information panel was combined with colour label elements, monochrome information had lower entropy than coloured label information. The study emphasises the possibility of producing a variety of effects on consumer attention by strategically placing monochrome and colour label elements in food label systems. Scan path entropy should be considered when evaluating label designs that are meant to highlight specific information for a variety of purposes, such as marketing, health communications, and safety messages. The use of monochrome or colour label components appears to influence observed entropy in label systems where information competes for consumer attention, and observed entropy can be influenced by the placement and combinations of various label elements that can be measured and adapted to achieve message attention goals.